Social Ontology of Allamah Tabataba'i' - Zaidi, Syed Zeeshan Haider (Technium Social Sciences Journal, 2021)
Although the term social ontology has emerged recently but ancient research regarding nature of social phenomenon caused questions that remained active today: what realities are produced by humans and which are created by nature? What is social creation? How social entity is created? Among Muslim scholars Allamah Tabataba'i' is the first philosopher who tried to answer mentioned questions and presented a theory around ninety years ago regarding social ontology. Apparently Allamah believes that perception and knowledge is same thing and there is no difference between them. Real perception always represents and shows an object out of our intellect and mind in external world. This object has its own existence and affects regardless the condition of knower. Human can create concepts due to his emotions which are emerged in result of his needs to live. These concepts are dependent upon mentioned emotions, remove needs and are eliminated or changed with elimination or change in emotions. This process of making concepts is called suppositional perception. Animal and man have suppositional perceptions along with real perception; they make these perceptions by making relation of necessity between themselves and the result of their actions. The purpose of these perceptions is to create high level of motivation in man so that he can perform actions which are required for their life and survival. Eventually, these perceptions lead to create social entities such as ownership and government.